KONSEP MASLAHAT DALAM PANDANGAN SA’ID RAMADHAN AL-BUTHI - Nanda Himmatul Ulya (Al-Maslahah : Jurnal Ilmu Syariah, 2019)
The phenomenon of the use of the human mind that sometimes exceeded the limits in the terminology of Islamic law became a restlessness of Muhammad Sa`id Ramadhan Al-Buthi. Maslahat (goodness) in the view of Sa`id Ramadhan Al-Buthi was not an argument that was independent but must be supported by other propositions. Therefore, responding to this phenomenon, He created a limitation in the concept of goodness. According to him, as stated in his book Dlowabith al-Maslahah fi al-Shari`ah al-Islamiyyah, Maslahat could be accommodated into Islamic law if it fulfilled several criteria as follows: first, that the goodness was still within the scope of Shariah purposes (Maqashid al-Syar`iyyah). Second, it did not contradict the Holy Qur`an. Third, it was not contrary to sunnah. Fourth, it did not contradict with qiyas. Fifth, it did not conflict with higher maslahat. Thus, in the view of Sa`id Ramadhan Al-Buthi concept of the charity included hifdz ad-din, hifdz an-nafs, hifdz al-aql, hifdz an-nasl, hifdz al-mal. Its implementation was certainly based on the order. The higher maslahat has to be taken precedence over form the lower. Last but not least, Al-Maqashid Al-Syar`iyyah was the goal of Islamic Law to achieve the maslahat of humanity both in the world and the hereafter.